THE EFFECT OF PRICE PERCEPTION AND SERVICE QUALITY ON BRAND IMAGE FOR IMPROVING INTEREST IN USING GO-JEK (Study On GO-JEK In Semarang City) - Nugraha, Septy Setia (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2018)
This research is conducted to test how big influence of price perception and service quality to brand image in increasing interest to use go-jek.Â  Samples were taken from the company's services go-jek number of 110 respondents, Structural Equation Modeling (SEM) was run by AMOS software, was used to analyze the data obtained, the analysis shows that the perception of price and service quality has a positive effect on the image of the brand in increasing interest in using. The most dominant variable in influencing interest in using with the mediation of brand image is the perception of price and service quality. The suggested implications are that the mock companies are able to create a brand image through competitive prices, easy payment systems and improved service quality